ChemInform Abstract: Base‐Promoted N‐Pyridylation of Heteroarenes Using N‐Propargyl Enaminones as Equivalents of Pyridine Scaffolds. Issue 52 (10th December 2015) - Cheng, Guolin; Weng, Yunxiang; Yang, Xifa; Cui, Xiuling
Abstract: N‐Propargyl enaminones, either in isolated form or generated in situ, are established as masked polysubstituted pyridine cores.